Hugo Black : the Alabama Years. - Hamilton, Virginia Van Der Veer (University of Alabama Press, 2014)
"Hamilton writes well and Alabama politics is always fascinating. As narrative history the book is outstanding, and it is easily the best study of Black's political career."-- American Historical Review.